2008
DOI: 10.1007/s10535-008-0114-4
|View full text |Cite
|
Sign up to set email alerts
|

Response of the cherry rootstock to water stress induced in vitro

Abstract: The in vitro response of sweet cherry (Prunus cerasus × P. canescens) rootstock Gisela 5 to increasing water deficit in the culture medium was studied. Water stress induced by the incorporation of 1, 2 and 4 % polyethylene glycol (PEG-8000) into the Murashige and Skoog medium was applied for 6 weeks. PEG-induced water stress reduced shoot dry mass, length, water content and relative chlorophyll content. Water stress also induced leaf necrosis without causing loss of viability in the explants. The increase in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 22 publications
7
34
0
2
Order By: Relevance
“…The Mn-SOD is resistant to both inhibitors; Cu/Zn-SOD is sensitive to both inhibitors whereas; Fe-SOD is resistant to KCN and sensitive to H2O2 (Ahmad et al, 2008;Gill and Tuteja, 2010;Karuppanapandian et al, 2011). There have been many reports of the increased activities of SOD under abiotic stresses induced with tissue culture techniques in a wide range of plant species, including heavy metals, such as Al, Cd, Cr, and Cu, hyperhydricity, salinity, gamma radiation, and drought (Gallego et al, 2002;Saher et al, 2004;Dewir et al, 2006;Israr et al, 2006;Erturk et al, 2007;Dasgupta et al, 2008;Sivritepe et al, 2008;Gupta and Prasad, 2010;Shehab et al, 2010;Yang et al, 2010;El-Beltagi et al, 2011;Helaly and El-Hosieny , 2011;Lokhande et al, 2011;Sen and Alikamanoglu, 2011;Xu et al, 2011;Patada et al, 2012) on the other hand, Fe-deficiency stress reduced activity of SOD (Lombardi et al, 2003). Advanced-antioxidant defense systems play an important role in plants not only to tolerate environmental stress but also to improve plants against these stresses.…”
Section: Antioxidant Defence Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The Mn-SOD is resistant to both inhibitors; Cu/Zn-SOD is sensitive to both inhibitors whereas; Fe-SOD is resistant to KCN and sensitive to H2O2 (Ahmad et al, 2008;Gill and Tuteja, 2010;Karuppanapandian et al, 2011). There have been many reports of the increased activities of SOD under abiotic stresses induced with tissue culture techniques in a wide range of plant species, including heavy metals, such as Al, Cd, Cr, and Cu, hyperhydricity, salinity, gamma radiation, and drought (Gallego et al, 2002;Saher et al, 2004;Dewir et al, 2006;Israr et al, 2006;Erturk et al, 2007;Dasgupta et al, 2008;Sivritepe et al, 2008;Gupta and Prasad, 2010;Shehab et al, 2010;Yang et al, 2010;El-Beltagi et al, 2011;Helaly and El-Hosieny , 2011;Lokhande et al, 2011;Sen and Alikamanoglu, 2011;Xu et al, 2011;Patada et al, 2012) on the other hand, Fe-deficiency stress reduced activity of SOD (Lombardi et al, 2003). Advanced-antioxidant defense systems play an important role in plants not only to tolerate environmental stress but also to improve plants against these stresses.…”
Section: Antioxidant Defence Systemmentioning
confidence: 99%
“…suspension cultures and callus cultures) and organized tissue (i.e. axillary shoot, shoot tip, mature embryo, whole plant) levels (Sivritepe et al, 2008;Cui et al, 2010;Shehab et al, 2010;Patada et al, 2012). Additionally, plant tissue culture techniques also allow opportunities for the researcher to improve plants against abiotic stress factors with the in vitro selection method (Jain, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molassiotis et al (2006) have reported Fe decrease in response to water stress. However, water deficit did not significantly influence Zn content in cherry rootstock Gisela (Sivritepe et al, 2008). The content of Fe and Zn in leaf tissue of Chlorophytum borivilianum was increased by both water deficit and waterlogging stresses.…”
mentioning
confidence: 82%
“…K, Ca, Mn, Zn ve Fe içerikleri bakımından her üç türde de kuraklık stresi bitkiler üzerinde olumsuz etki yapmıştır. Nitekim oksidatif stres ile birlikte K, Ca, Fe ve Mn konsantrasyonlarında azalma meydana geldiği belirtilmektedir [52]. Bitkilerde K iyonunun aktif alımıyla hücrelerdeki ozmotik potansiyel yükseltilmekte ve böylece bitkiye su girişi mümkün olabilmektedir.…”
Section: Materyal Ve Yöntemunclassified